QUALITY OF CURED FISH FROM THE MAHARASHTRA COAST - JOSEPH, K GEORGE; MURALEEDHARAN, V; NAIR, T. S UNNIKRISNAN; KALAIMANI, N (Fishery Technology, 2017)
Chemical, bacteriological and organoleptic characteristics of sun dried/drysalted fish collected from five major centres of coastal Maharastra are reported. Wide variations are seen in the quality of the different samples. In dry salted products, moisture ranged from 16.17 to 46.58 %; salt from 5.18 to 22.75 %; acid insoluble ash from 1.0 to 6.83 %. In sun dried samples moisture varied from 16.15 to 39.51 % and acid insoluble ash from 0.42 to 2.82 %. The sun dried samples, though no salt was used in the process, showed fairly good amount of salt.